Being There While Not Being There: Reflections on Multi-sited Ethnography and Field Access in the Context of Forced Migration. Issue 2 (1st September 2021) - McAdam-Otto, Laura K.; Nimführ, Sarah
Abstract: Multi-sited research has become a quality criterion for ethnographic research. This applies especially to studies on forced migration. Here, a site is often equated with a state, where researchers are usually required to be physically present. In this article, however, we ask: Must multi-sited research necessarily be multi-national? Do researchers have to be physically present at all sites? By discussing ethnographic material collected with forced migrants in Malta, we demonstrate that multi-sitedness is viewed in too narrow terms when site is equated with the nation-state. Adopting this approach also obscures refugees' lived realities, their patterns of movement and their often truncated mobility. Instead, we carve out an understanding of multi-sited ethnography within one locality, introducing the concept of un-participated sites to include sites researchers are not able to physically visit. While the inaccessibility of sites is often inherent to ethnographic studies, it is all the more relevant for migration research.